Adsorption of anthraquinone dye onto eco-friendly semi-IPN biocomposite hydrogel: Equilibrium isotherms, kinetic studies and optimization - Oladipo, Akeem Adeyemi; Gazi, Mustafa; Saber-Samandari, Samaneh (Elsevier Science Bv, 2014)
This work demonstrates the use of a new eco-friendly semi-IPN cellulose-graft-polyacrylamide/hydroxyapatite biocomposite hydrogel (EBH), for efficient dye removal from aqueous solution. Here, novel eco-friendly biocomposite hydrogels were prepared from grafted cellulose and hydroxyapatite, and the resulting biocomposites were well characterized. Adsorption characteristics of the as-prepared composite hydrogel were tested by using anthraquinone dye, reactive blue 2 (RB2) as an adsorbate. The sorption kinetics, isotherms, and thermodynamics of RB2 onto the composite hydrogel have been assessed at various operation conditions such as composite dosage, solution pH, temperature, contact time and initial dye concentration. The equilibrium data followed both Redlich-Peterson and Langmuir models. It was found that RB2 adsorption process followed the pseudo-second-order kinetics, as well as the Elovich model. The thermodynamic data indicated that RB2 adsorption onto the composite hydrogel was endothermic and spontaneous. Box-Behnken design was employed to ensure high efficiency and also to optimize the adsorption parameters of RB2 onto EBH. On the basis of the obtained data, we conclude that the composite hydrogel being low-cost and eco-friendly adsorbent might be a reliable alternative to remove hazardous anthraquinone dyes, pigments and heavy metals from aqueous solutions. (C) 2013 Taiwan Institute of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Anthraquinone dye; Cellulose; Hydroxyapatite; Box-Behnken; Eco-friendly